Studies of encapsulation of a new potential antitumoral indole derivative in nanoliposomes for drug delivery applications - Castanheira, Elisabete M. S. (2010)
This work was funded by FCT-Portugal and FEDER through CFUM, CQ-UM, Project PTDC/QUI/81238/2006 and Post-doc. grant of A.S. Abreu (SFRH/BPD/ /24548/2005).